From Arab nationalism to OPEC : Eisenhower, King Saʻūd, and the making of U.S.-Saudi relations - Citino, Nathan J. (Indiana series in Middle East studies., 2002)
Citino provides a framework for understanding the transition from British imperial hegemony to an American capitalist order in the Middle East, and the historical antecedents of America's leading role in the Gulf War.